If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(2X + 5) = 4X + 18 Reorder the terms: -6(5 + 2X) = 4X + 18 (5 * -6 + 2X * -6) = 4X + 18 (-30 + -12X) = 4X + 18 Reorder the terms: -30 + -12X = 18 + 4X Solving -30 + -12X = 18 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. -30 + -12X + -4X = 18 + 4X + -4X Combine like terms: -12X + -4X = -16X -30 + -16X = 18 + 4X + -4X Combine like terms: 4X + -4X = 0 -30 + -16X = 18 + 0 -30 + -16X = 18 Add '30' to each side of the equation. -30 + 30 + -16X = 18 + 30 Combine like terms: -30 + 30 = 0 0 + -16X = 18 + 30 -16X = 18 + 30 Combine like terms: 18 + 30 = 48 -16X = 48 Divide each side by '-16'. X = -3 Simplifying X = -3
| 44-2+6y-10= | | 9/5(10)=32 | | 3(d+7)=81 | | 3x^2-6x^2-72x= | | 63+6x-3=90 | | 4x=200-6x | | x/5-2=12 | | 3.5x+5.75y=1200 | | 0.3+1.75=6.25 | | U/2=9 | | 4x+1=-10x-5 | | 54=5-d | | P-13=26 | | 7/3=y/10 | | 1/x=1/2/4/5 | | -7(n-84)=-91 | | 6x^4-10x-6x^2= | | 2x+6-8= | | -2x+45+8x+21=90 | | 2a^4-32b^4=0 | | 3x+7=12+7 | | 41-n=-57 | | 3/5/2=1/4/x | | Y=-2/5x-8 | | 13x-16+6x+30=90 | | 72=8(q+4) | | -5a(b-2c)= | | 4(q+15)-4=8 | | 10y-5y-10=80.20 | | N+36=4 | | 2/3=1/2/x | | 12k-1=3+5k |